KESIAPAN GURU SEKOLAH DASAR DALAM PELAKSANAAN PEMBELAJARAN TEMATIK INTEGRATIF PADA KURIKULUM 2013 - Anna Astiningtyas (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2018)
This study aims to implement the readiness of teachers in integrative thematic teaching facing the 2013curriculum. The background of the importance of the readiness of elementary school teachers in facing the 2013curriculum is by implementing integrative thematic learning in the learning process. The data collected involves10 research journals to compare teacher preparedness outcomes and the data can be analyzed using percentresults. The results show that theoretically the teacher already has an understanding of the curriculum 2013, butstill lacking in the implementation. Actually the motivation of teachers in implementing instructional innovationis very high, unfortunately it is less supported than facilities, facilities and infrastructure. Readiness of teachersin implementing the 2013 curriculum is included in the high category. Teachers have high expectations for theimplementation of the 2013 curriculum to have a positive impact on the quality of learning. This study usesdocument studies from the results of previous studies. Data collection is done by searching for the GoogleScholarly electronics journal. From the search results obtained, each model selected 10 journals for furtheranalysis in percent (%) form. From the results of the analysis of the readiness of elementary teachers in theimplementation of integrative thematic learning can be seen from the lowest 4.2% to the highest 35% with anaverage of 17.3%.